Investigating the Mechanism of Unilateral Cross Incompatibility in Longan (Dimocarpus longan Lour.) Cultivars (Yiduo × Shixia) - Wang, Jing; Chen, Ji; Huang, Shilian; Han, Dongmei; Li, Jianguang; Guo, Dongliang (Frontiers in Plant Science, 2022)
Longan (Dimocarpus longan Lour.) is an important subtropical fruit tree in China. Nearly 90% of the longan fruit imports from Thailand are from the cultivar Yiduo. However, we have observed that there exists a unilateral cross incompatibility (UCI) when Yiduo is used as a female parent and Shixia (a famous Chinese cultivar) as a male parent. Here, we performed a comparative transcriptome analysis coupled with microscopy of pistils from two reciprocal pollination combinations (Shixia♀ x Yiduo♂ (SY) and Yiduo♀ x Shixia♂ (YS) at 4, 8, 12, and 24 hours after pollination. We also explored the endogenous Jasmonic acid (JA) and Jasmonyl isoleucine (JA-Ile) levels in pistils of the crosses. The microscopic observations showed that the UCI was a sporophytic incompatibility. The endogenous JA and JA-Ile levels were higher in YS as compared to SY at the studied time points. We found 7,251 differentially expressed genes from the transcriptome analysis. Our results highlighted that the genes associated with JA biosynthesis and signaling, pollen tube growth, cell-wall modifications, starch and sucrose biosynthesis, and protein processing in endoplasmic reticulum pathways were differentially regulated between SY and YS. We discussed the transcriptomic changes in the above-mentioned pathways regarding the observed microscopic and/or endogenous hormone levels. This is the first report on the elaboration of transcriptomic changes in longan reciprocal pollination combination showing UCI. The results presented here will enable the longan breeding community to better understand the mechanisms of UCI.